Girls and Assassin’s Creed - Veronique Bailey (Bina Nusantara University, 2017)
Assassins Creed is one of the top selling video game franchises], as such it has a marked impact on the worldwide culture of gaming. As interaction designers we have to evaluate the impact that video games have on their users. One way that we can do that is by taking a more feminist approach; feminism naturally goes hand in hand with interaction design as it refers to fulfillment, identity, equity, empowerment and social justice. In this paper I evaluate the user satisfaction of female users as they play Assassinâ€™s Creed (An Action Adventure game) in terms of evaluating their levels of fulfillment, identity, equity and empowerment.Â